Pemahaman Masyarakat Desa Tanjung Luar Terhadap Pentingnya Ekosistem Mangrove Dalam Pelestarian Lingkungan Pesisir - Erlina; Izam Mahendra; Sipta Liana; Baiq Susmita Rauhillah; Lalu Rezqy Gempita Sakti; Huldiya Syamsiar (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
The mangrove ecosystem is a coastal ecosystem that plays a vital role in maintaining environmental balance through its coastal protection function, providing habitat for various marine biota, and supporting the sustainability of fisheries resources. This study aims to determine the understanding of the community of Tanjung Luar Village, Keruak District, East Lombok Regency, regarding the importance of mangrove ecosystems in coastal environmental conservation. The study used a descriptive method with a qualitative approach. Data were collected through semi-structured interviews with fishermen, community leaders, village officials, and coastal communities, and supported by various relevant literature sources. The results showed that most people understood the benefits of mangroves as coastal protection from abrasion and as a habitat for various marine biota that support the livelihoods of fishermen. However, community knowledge regarding the function of mangroves as carbon sinks (Blue Carbon) and maintains the balance of coastal ecosystems still needs to be improved. Differences in education levels, experience, and access to information are factors that influence community understanding. Therefore, ongoing education and outreach programs are needed to increase awareness and encourage community participation in maintaining the sustainability of mangrove ecosystems.